2005
DOI: 10.1097/01.yco.0000186814.08826.db
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and geriatric psychiatry: a neglected field

Abstract: Malnutrition is likely to have considerable impact on the mental and physical state of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
0
13
0
2
Order By: Relevance
“…For the clinical practitioner, our results on the one hand highlight the need for nutritional screening of elderly people presenting with mental health symptoms. Both in somatic and psychiatric settings, nutrition have often been neglected [3,36]. Screening for malnutrition can easily be performed by the use of instruments like the 'MUST' tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the clinical practitioner, our results on the one hand highlight the need for nutritional screening of elderly people presenting with mental health symptoms. Both in somatic and psychiatric settings, nutrition have often been neglected [3,36]. Screening for malnutrition can easily be performed by the use of instruments like the 'MUST' tool.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression, often seen as co-morbid conditions with overlapping symptoms [1], are the two most frequent mental health disorders [2]. Malnutrition is also relatively common in elderly individuals and may be associated with mental health, particularly depression [3]. …”
Section: Introductionmentioning
confidence: 99%
“…This may in turn be of special importance to EQ5D dimensions like self-care and usual activities, both significantly associated with the risk of malnutrition in the present study. Furthermore, malnutrition may affect the mental health of elderly individuals adversely, thereby reducing HRQoL [25]. Malnutrition may also be associated with diseases and conditions, which in turn decrease HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although well-known changes in micronutrient status in old age significantly correlate with adverse physical outcomes such as cardiovascular, disease, cerebrovascular disease, impaired immune function, and bone health, which in turn contribute to the development of frailty, less is known about a relationship between B 12 , folate, and quality of life. 16 However, there is evidence of a strong link between B 12 and folate status and depression in older adults. 17 The recent National Diet and Nutrition Survey of older persons from the United Kingdom, where the study sample of the current trial came from, identified low biochemical con-centration of one or more micronutrients in 40% of the population.…”
Section: Discussionmentioning
confidence: 99%